2015
DOI: 10.1038/srep09806
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Study of Surface Modified Poly(ethylene glycol)-Impregnated Sintered Bovine Bone Scaffolds on Human Fibroblast Cells

Abstract: Scaffold design from xenogeneic bone has the potential for tissue engineering (TE). However, major difficulties impede this potential, such as the wide range of properties in natural bone. In this study, sintered cortical bones from different parts of a bovine-femur impregnated with biodegradable poly(ethylene glycol) (PEG) binder by liquid phase adsorption were investigated. Flexural mechanical properties of the PEG-treated scaffolds showed that the scaffold is stiffer and stronger at a sintering condition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 66 publications
3
31
0
1
Order By: Relevance
“…Fourier transform infrared (FTIR) spectroscopy was used to probe the interaction between the PEG molecules and the zinc surface . Few stretching vibrations were observed that are specific to the PEG200 polymer: a large vibration between 3600 cm −1 and 3200 cm −1 representing hydroxyl stretching, ∼1400 cm −1 corresponding to C−H bending and scissoring, ∼1160 cm −1 for the symmetric C−O‐C stretching, ∼1100 cm −1 indicating C−O stretching, ∼1060 cm −1 denoting CO−C axial deformation, and ∼966 cm −1 signifying C−C stretching ,. Zinc electrodes were exposed to several types of electrochemical tests to investigate the response of PEG in the electrolyte.…”
Section: Resultsmentioning
confidence: 99%
“…Fourier transform infrared (FTIR) spectroscopy was used to probe the interaction between the PEG molecules and the zinc surface . Few stretching vibrations were observed that are specific to the PEG200 polymer: a large vibration between 3600 cm −1 and 3200 cm −1 representing hydroxyl stretching, ∼1400 cm −1 corresponding to C−H bending and scissoring, ∼1160 cm −1 for the symmetric C−O‐C stretching, ∼1100 cm −1 indicating C−O stretching, ∼1060 cm −1 denoting CO−C axial deformation, and ∼966 cm −1 signifying C−C stretching ,. Zinc electrodes were exposed to several types of electrochemical tests to investigate the response of PEG in the electrolyte.…”
Section: Resultsmentioning
confidence: 99%
“…An X-ray diffractometer (Empyrean, PANalytical, Almelo, The Netherlands) was used to obtain the different X-ray diffraction (XRD) patterns of the developed electro-ceramics using Cu-Kα radiation in the 2θ range of 20°–50°. Density ( ρ , g/cc), open porosity (%), and water absoption (%) ability of electro-ceramics were measured following Equations (1)–(3), respectively, with the help of a modified Archimedes’ principle as highlighted in our previous studies [42,43]: ρ=WbiWaiWdi×ρwater25 °C Popen=WaiWbiWaiWdi×100 Absorbed water= WaiWbiWbi×100  where W bi , W di and W ai represent the initial dry weights of the samples in air before immersion in water, in water during immersion in water, and in air after immersion in water, respectively. The resolution of the weighing machine was ±0.0005 g. At least five identical specimens were prepared to calculate the standard deviation (SD) of all the sintered samples, where ρwater25 °C represents the water density at tested temperature 25 °C.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of humidity measurement, it is also important to measure a high precision porosity of small specimens [30]. The pore size distribution (PSD) of unsintered and sintered (1050 °C) materials was analyzed from the inverted images of their corresponding FESEM micrographs using ImageJ software 1.46 r, as this technique is considered the best method for studying the porosity of ceramic–polymer composites [31]. Density (ρ, g/cc), open porosity (%), and absorbed water or water absoption (%) present in the porous materials were measured in water following Equations (1)–(3), respectively, using modified Archimedes’ principle explored in our previous studies [32,33].…”
Section: Methodsmentioning
confidence: 99%